Synthesis and Pharmacological Activity of Some Schiff Bases Derived from Substituted 1,2,4-Triazoles - Ishwar Bhat, K.; Kumar R., Vinod; Kalluraya, Balakrishna (Asian Journal of Chemistry, 2012)
A new series of Schiff bases of 3-substituted-4-amino-5-mercapto-1,2,4-triazoles have been synthesized. Structures of these Schiff bases have been confirmed by analytical and spectral data and they have been screened for antibacterial, antifungal and anti-inflammatory activity.